SUSTAINABLE OPERATIONS AS A STRATEGY OF MANAGEMENT OF COMPANIES, WITH A REVIEW IN THE FIELD OF AGRICULTURE - Rajnović, Ljiljana; Cico, Snežana; Eremić – Đorđić, Jelica (Economics of Agriculture, 2019)
The operation of companies on the domestic or international market implies, a well - organized company whose function is based on efficient business and, on the fiduciary duty of the owner and management, which is at the same time a challenge, but also a great responsibility in view of the interests of all constituents. The disadvantage or loss of these features in organizing the companies, leads to significant lagging of the company in relation to its competitors and the continuous weakening of economic power can lead to the collapse, which is the hardest blow to the investors but also the recognition of the manager that he was not successful. The agriculture is one of the most important sector of activity in Serbia, in the last hundred years, in terms of the volume of production and the number of engaged population, which is why sustainable business in this area is necessary.